Effects of oxygen saturation on the hypoxia-inducible factor-1?, subfatin, asprosin, irisin, c-reactive protein, maresin-1, and diamine oxidase in diabetic patients with COVID-19 - Karagoz, Z. Karaca; Aydin, S. (Verduci Publisher, 2022)
OBJECTIVE: Oxygen is essential for living organisms that perform aerobic respi-ration since cells begin to die when humans and animals are deprived of oxygen. Oxygen satura-tion decreases and shortness of breath occurs in coronavirus (COVID-19) disease. Therefore, in this study, we aimed to determine the changes in hypoxia-inducible factor-1 alpha (HIF-1 alpha), subfatin, asprosin, irisin, C-reactive protein (C-RP), Ma -resin-1 (MaR-1), and diamine oxidase (DAO) mol-ecules in diabetic patients with coronavirus ac-cording to their oxygen saturations.PATIENTS AND METHODS: Participants were classified into 4 Groups of 22, including pa-tients with oxygen saturation between 95% and 100% (Group I, control), between 80% and 85% (Group II), between 75% and 79% (Group III), and between 70% and 74% (Group IV). COVID-19 was diagnosed with PCR testing and 5 mL of blood was taken following the diagnosis. HIF-1 alpha, sub-fatin, asprosin, irisin, MaR-1, and DAO values of the participants were measured with ELISA. Other parameters used in the study were ob-tained from the records of the patients.RESULTS: When Group I was compared to Groups II, there was no significant change in Group II while HIF-1 alpha, subfatin, asprosin, irisin, C-RP, and DAO counts had increased signifi-cantly in Groups III and IV. When the MaR-1 val-ues were examined, they were reported to have decreased significantly in Groups III and IV (p < 0.05). Similarly, when Group II and Group IV were compared, HIF-1 alpha, subfatin, asprosin, iri-sin, C-RP, and DAO values of the participants in Group IV had significantly increased while MaR-1 values had significantly decreased (p < 0.05). In the case of oxygen saturation decreasing be-low the critical value (70-74%) in patients withcoronavirus, the release of HIF-1HIF-1 alpha, sub-fatin, asprosin, irisin, C-RP, and DAO increased while the MaR-1 values decreased (p < 0.05). CONCLUSIONS: Changes in these molecules in patients with coronavirus and diabetes ac-cording to their oxygen saturation suggested that they functioned as the metabolic oxygen sensors of the metabolism. Therefore, accord-ing to these data, it was predicted that these molecules had the potential to be used in the di-agnosis and follow-up of diseases related to ox-ygen (such as asthma, and critical intensive care patients) in clinics in the future.
Keywords: Oxygen saturation; Hypoxia-inducible factor-1?; Subfatin; Asprosin; Irisin; C-reactive protein; Mares-in-1; Diamine oxidase; Diabetes mellitus; COVID-19